EFFECT OF DIETARY PARTIAL REPLACEMENT OF FERMENTED POTATO PEELS POWDER ON PHYSIOLOGICAL AND MICROBIAL PARAMETERS OF BROILERS - AL-Shemmari , W. H.; AL-Mashhadan, H. A. i (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The experiment was carried out to investigate the effect of dietary replacement of fermented potato peels powder (FPPP) with Kiwi juice or probiotics with yellow corn on pre- and post- storage of meat oxidation for 30 days, physiological and microbial of broiler. A total of 231, day old broiler chicks (Rose 308) were used. The chicks were randomly distributed to seven treatments, with 3 replicate per each (11 chicks/ replicate): 6 males and 5 females. Chicks in the first treatment were fed on an ordinary diet and it was considered as a control treatment (T1). The T2, T3 and T4 treatments were considered as replacement treatments in which the (FPPP) by Kiwi juice was replaced by yellow corn at level of 6, 12 and 18% respectively. The T5, T6 and T7 treatments were used (FPPP) by Iraqi probiotics replaced by yellow corn at level of 6, 12 and 18% respectively. Significant differences (P≤0.01) were showed among treatments in the oxidation indices so that all the replacement treatments were superior in the oxidation value as compared with control at pre- and post - meat storage period. No significant differences was found in glucose concentration, total protein, uric acid and liver enzymes. The histological in Ileum showed superiority (P≤0.01) in crypt depth of T3, T6 and T7 while T6 significantly (p>0.01) villus length and the mucosal layer thickness as compared with T1. Excluding data of T1 and T2 groups, all treatments have a crucial role in increasing beneficial bacterial count.